Indicadores de sustentabilidade na avaliação do sistema de cultivo de Tilápia do Nilo em tanques-rede no reservatório de Santa Cruz, Apodi-RN - Moura, Rodrigo Sávio Teixeira de (Universidade Federal Rural do Semi-Árido, 2014)
The global fish consumption has increased rapidly in recent years and aquaculture contributes increasingly to meet this demand for fish. It is important, however, to establish standards and methods to assess this sustainability in order to analyze the situation of production systems currently in use. The indicators come to be a powerful tool because it allows to obtain a holistic view of the production system in its environmental, social, and economic aspects. Thus, the aim of this study was to evaluate the sustainability of the cage farming system developed in the reservoir of Santa Cruz, Apodi-RN , on their environmental, social and economic aspects . For that were calculated the nutrients and particulate material sedimentation rates in the reservoir, and were used a set of 49 sustainability indicators which were modeled within the Drivers-Pressure-State-Impact-Response (DPSIR) framework. The results indicate that the culture system is economically feasible, generating profit and distributing income, thereby enabling their viability over time. However, the capital generated benefits just a few people, and it is not fixed in the community. Environmentally speaking, the system was inefficient in the use of resources, especially nitrogen and phosphorus, and most of these resources are not incorporated into biomass but sedimented in the reservoir. For the social dimension, the enterprise employs little, generating little direct employment. We realize that fish farming changes the water characteristics of the reservoir, and the indicators used along with the DPSIR modeling were able to satisfactorily reflect these influences
Sustainability indicators in the evaluation of the Nile Tilapia cage growing system in the Santa Cruz reservoir, Apodi-RN
Keywords: Sustainable IAquicultura; Nile tilapia; Sustainability modeling; Aquicultura sustentável; Tilápia do Nilo; Modelagem da sustentabilidade; CIENCIAS AGRARIAS::MEDICINA VETERINARIA